Pengolahan Selai Tomat sebagai Prodak Bernilai Ekonomi Tinggi Di Desa IV Suku Menanti - Andriani, Evi; Nur’aini , Hesti; Arif , Hilda Meisya; Darius, Darius; Anjaly , Ana (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The characteristics of tomatoes which generally have a relatively high water content cause tomatoes to be easily damaged, have a relatively short shelf life, are susceptible to attacks by microorganisms, both pests and plant diseases, and are very easy to experience physical changes. So tomatoes have the potential to be processed into tomato jam which has high economic value. The purpose of the community service activity is to provide skills in processing and packaging tomato jam to the community in Village IV Suku Menanti. The method of implementing the activity is in the form of socialization, question and answer discussions and practices for processing and packaging tomato jam. By carrying out this activity, the Village Community will understand more about the diversification of tomato processing and have skills in tomato jam processing and packaging technology.